Uma proposta de interface de consulta para recuperação de informação em documentos semi-estruturados - Junqueira, Mirella Silva (2009)
Semi-Structured Information Retrieval is an intermediate way to retrieve information between Textual Retrieval and Structured Retrieval (typical in relational database systems). In structured retrieval systems, users generally know the available data structure and query languages, so they can formulate queries that produce more accurate results. In textual retrieval users dont known the data structure and formulate queries with keywords only, which produces not so accurate results. In Semi-Structured Retrieval, users generally dont known the data structure and formulate queries that mix textual search and structured retrieval mechanisms. In this context, the problem of how to improve the results accuracy using the structure inside semi-structured documents appears. Semi-structured data is usually stored as XML documents and can be seen as trees. Internal nodes of these trees have the structure of documents, while leaf nodes contain text. The design of interfaces for users in this context is one of the biggest challenges in semi-structured information retrieval. This occurs especially because the users dont known the document structure and have problems in formulating structured queries. This dissertation presents a proposal and a prototype interface developed to help users in the process of formulation of structured queries. The aim is to increase the precision in the results of the queries. The proposal is validated by experiments involving volunteers users and by comparing the results of textual queries and structured queries made with the help of the interface. The improvement reaches 440% for well structured queries, with a user who knows the interface, and 179.75% for reasonably structured queries, by users without experience to use the interface.